Use of artificial intelligence in the diagnosis, treatment and surveillance of patients with kidney cancer - Timofeeva, E. Yu; Azilgareeva, С. R.; Morozov, A. O.; Taratkin, M. S.; Enikeev, D. V. (Vestnik urologii (Online), 2023)
Currently, artificial intelligence (AI) has developed greatly and has become the subject of active discussions. This is because artificial intelligence systems are constantly being improved by expanding their computing capabilities, as well as obtaining massive data. Due to this, AI can help to set a diagnosis and select the most effective treatment. The study aimed to analyse the possibilities of AI in the diagnosis, treatment and monitoring of patients with renal cell carcinoma (RCC). AI shows great prospects in the diagnosis urinary system lesions, in the ability to differentiate benign and malignant neoplasm (due to machine learning systems), as well as in predicting the histological subtype of the tumor. AI can be used at the intraoperative stage (thanks to the integration of virtual 3D models during surgical interventions), which reduces the frequency of thermal ischemia and damage to the kidney cavity system. AI finds its application in histopathological evaluation: the AI model reaches 100.0% sensitivity and 97.1% specificity in the differential diagnosis of normal tissue from RCC. AI model algorithms may be used to identify patients at high risk of relapse requiring long-term follow-up, as well as to develop individual treatment and follow-up strategies. All the above proves the possibility of using AI in all stages of the management of patients with RCC. The implementation of AI in medical practise opens new perspectives for the interpretation and understanding of complex data inaccessible to clinicians.